Traceability of domestic carnivores in France - Chaisemartin, D (Revue scientifique et technique (International Office of Epizootics), 2001)
The traceability of domestic carnivores facilitates the monitoring of such animals for health purposes and for the management of suspected contagious diseases. A traceability system can also assist in the detection of fraud, lost or stolen animals, and in finding owners. To be effective, a system for the ongoing monitoring of these animals and their movements is required. Marking domestic carnivores is insufficient; a reliable identification system, with adequate guarantees of functioning, must include procedures to monitor the assignment of identification numbers, the marking methods (tattooing or electronic identification), in addition to the printing, issuing and registration of identification cards and the computerised management of data regarding the animals and changes of address or owner. The equipment used in the identification procedure must be well understood and employed correctly so that the identity of the animal is clear to all and verifiable by the appropriate authorities. The equipment must therefore be subject to approval, and must meet pre-defined specifications. For these reasons, France has adopted certain measures, including the establishment of a national register, the compulsory compliance with ISO 11784 and 11785 standards, and a transponder identification number including the country code (250 for France), the species code, and the identification code of the manufacturer.